New Persistent Opioid Use After Orthopaedic Foot and Ankle Surgery: A Study of 348 Patients. Issue 16 (15th August 2021) - Hejna, Emily E.; Mehraban, Nasima; Holmes, George B.; Lin, Johnny L.; Lee, Simon; Hamid, Kamran S.; Bohl, Daniel D.
Abstract : Introduction: The opioid epidemic is a devastating public health issue to which orthopaedic surgery is inextricably linked. The purpose of this study was to identify risk factors for new persistent opioid use after orthopaedic foot and ankle surgery among patients who were opioid naive preoperatively. Methods: Patients undergoing orthopaedic foot or ankle surgery at a single institution were identified. Our state's prescription monitoring program was used to track opioid prescriptions filled in the preoperative (6 months to 30 days before surgery), perioperative (30 days before to 14 days after), and postoperative (2 to 6 months after) periods. Patients filling a prescription during the preoperative period were excluded. Baseline characteristics, surgical characteristics, and perioperative morphine milligram equivalents were tested for association with new persistent use during the postoperative period. Results: A total of 348 opioid-naive patients met the inclusion criteria. Overall, the rate of new persistent postoperative opioid use was 8.9%. Patients reporting recreational drug use had the highest risk, at 26.7% (relative risk [RR] = 3.3, 95% confidence interval, 1.3 to 8.2, P = 0.0141). In addition, patients who had perioperative opioid prescription >160 morphine milligram equivalents were at increased risk (RR = 2.2, 95% confidence interval, 1.1 to 4.5, P = 0.021). Other risk factors included age ≥40 years (RR = 2.2, P = 0.049) and consumption of ≥6 alcoholic beverages per week (RR = 2.1, P = 0.040). New persistent use was not associated with ankle/hindfoot surgery (versus midfoot/forefoot), bone surgery (versus soft-tissue), or chronic condition (versus acute; P > 0.05). Conclusion: The rate of new persistent postoperative opioid use after orthopaedic foot and ankle surgery is high, at 8.9%. Greater perioperative opioid prescription is a risk factor for new persistent use and is modifiable. Other risk factors include recreational drug use, greater alcohol use, and greater age. Orthopaedic foot and ankle surgeons should limit perioperative prescriptions and be cognizant of these other risk factors to limit the negative effects of opioid prescriptions on their patients and communities. Level of Evidence: Level III